Lavender essential oils-hidden relationships between the samples of origin - Ekaterina Kozuharova; Vasil Simeonov; Christina Stoycheva; Niko Benbassat; Daniela Batovska (Pensoft Publishers, 2024)
Lavender essential oil is an economically important ingredient in perfumery, the food industry, and pharmacy. There is notable diversity in the composition of lavender essential oils. The reasons are the high genetic diversity of lavender cultivars and the variety of ecological specifics in the regions of cultivation. The aim of this research is to check which lavender essential oil variety is best regarding the content of the most important components through comparative statistical tests. We created a data set of 88 lavender essential oil samples from 16 countries. The multivariate statistics (hierarchical and non-hierarchical clustering) and factor analysis reveal hidden relationships between the objects of the study (samples) or between the variables characterizing the objects (chemical descriptors-16 components). The results are discussed in detail. All samples from Bulgaria, together with a few of the Italian, French, Greek, Indian, and Chinese samples, fall into one cluster with the standard maximums. Graphical abstract: